Intratumoral STING agonist reverses immune evasion in PD-(L)1-refractory Merkel cell carcinoma: mechanistic insights from detailed biomarker analyses - Shailender Bhatia; Paul Nghiem; Rima Kulikauskas; Candice Church; David M Koelle; Lisa Tachiki; Kimberly Smythe; Thomas Pulliam; Shira Tabachnick-Cherny; Saumya Jani; Peter H Goff; Rashmi Bhakuni; et al. (Journal for ImmunoTherapy of Cancer)
Background Antibodies blocking programmed death (PD)-1 or its ligand (PD-L1) have revolutionized cancer care, but many patients do not experience durable benefits. Novel treatments to stimulate antitumor immunity are needed in the PD-(L)1 refractory setting. The stimulator of interferon genes (STING) protein, an innate sensor of cytoplasmic DNA, is a promising target with several agonists in development. However, response rates in most recent clinical trials have been low and mechanisms of response remain unclear. We report detailed biomarker analyses in a patient with anti-PD-L1 refractory, Merkel cell polyomavirus (MCPyV)-positive, metastatic Merkel cell carcinoma (MCC) who was treated with an intratumoral (IT) STING agonist (ADU-S100) plus intravenous anti-PD-1 antibody (spartalizumab) and experienced a durable objective response with regression of both injected and non-injected lesions.Methods We analyzed pretreatment and post-treatment tumor and peripheral blood samples from our patient with single-cell RNA sequencing, 30-parameter flow cytometry, T cell receptor sequencing, and multiplexed immunohistochemistry. We analyzed cancer-specific CD8 T cells using human leukocyte antigen (HLA)-I tetramers loaded with MCPyV peptides. We also analyzed STING expression and signaling in the tumor microenvironment (TME) of 88 additional MCC tumor specimens and in MCC cell lines.Results We observed high levels of MCPyV-specific T cells (12% of T cells) in our patient’s tumor at baseline. These cancer-specific CD8 T cells exhibited characteristics of exhaustion including high TOX and low TCF1 proteins. Following treatment with STING-agonist plus anti-PD-1, IT CD8 T cells expanded threefold. We also observed evidence of likely improved antigen presentation in the MCC TME (greater than fourfold increase of HLA-I-positive cancer cells). STING expression was not detected in any cancer cells within our patient’s tumor or in 88 other MCC tumors, however high STING expression was observed in immune and stromal cells within all 89 MCC tumors.Conclusions Our results suggest that STING agonists may be able to work indirectly in MCC via signaling through immune and stromal cells in the TME, and may not necessarily need STING expression in the cancer cells. This approach may be particularly effective in tumors that are already infiltrated by inflammatory cells in the TME but are evading immune detection via HLA-I downregulation.